THEORETICAL BASIS OF TECHNOLOGICAL PARAMETERS OF THE NEW PNEUMO-MECHANICAL GIN MACHINE - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The researchers made a significant contribution to the theoretical development of the ginning process. Having studied the composition of the raw material roller, the nature and speed of ginning, the theory of seed separation from the working chamber, the shape of the gin working chamber and the saw teeth, the cause of defects in the ginning process, and the possibility of covering the saw teeth, they found out that not all of them are uniformly covered with fiber and not all of them participate in the work process. They believe that it is necessary to improve the shape of the raw material chamber in order to facilitate the rotation of the raw material roller, increase the number of revolutions of the saw cylinder to 700 ... 730 min-1, reduce the relative speed of the roller compared to saws, and accelerate the removal of seeds from the center of the chamber.